Fintech as a Source of Financial Innovations on the Polish Financial Services Market - Karolina Anielak (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego)
The paper presents the definition of innovation, advancement and development of the Fintech sector on the global scale, with particular emphasis put on Poland. Fintechs, i.e. IT companies that provide increasingly more modern solutions for customers active on the financial markets are not fully described in the literature on the subject. The aim of the paper was to present a comprehensive definition of Fintech, show the scale of this type of ventures around the world and in Poland, and analyze the forms and potential of the cooperation of Fintech companies with financial services entities, in particular with the banks. The article uses a critical analysis of the literature of mainly English-language studies from the last 5 years, indicating the state of financial innovations and their importance on the global scale. The author analyzed statistical data from PWC Global Fintech Report, CitiGPS reports, Capgemini reports and KPMG, which enabled her to present the value of global investments in Fintech. The performed cause and effect analysis indicates that investments in the Fintech sector are becoming more and more popular, that this market will be growing due to cooperation, among others, with the banks which want to meet the requirements of their customers using more advanced technologies.